A multi-variable study of factors affecting the complex resistivity of conductive mortar. Issue 13 (15th March 2019) - Davey, Stephen; Paine, Kevin; Soleimani, Manuchehr
Abstract : Twenty-four mortar mixes were tested to assess the effects of mix design factors on complex electrical resistivity. Of these mixes, six were conventional and 18 were conductive mixes, containing varying quantities of either graphite or carbon fibre powder additions, which have been shown in previous studies to reduce the resistivity of cementitous materials. Complex resistance measurements from 20 Hz to 10 MHz taken between 7 and 35 d after casting were analysed. Comparisons were made between the effects on complex resistivity of varying quantities of additions, water/cement ratio and grit/sand ratio. In conventional mixes, the water/cement ratio was found to have more significance for complex resistance than the grit/sand ratio. Conductive additions were found to reduce the magnitude of complex resistivity as well as the influence of other mix factors. This novel and comprehensive comparison of the effects of three elements of mix design on complex resistance will be of use to anyone wishing to produce mortars or concrete for use in self-heating, self-sensing, or electrical property imaging contexts.